BUDAYA ORGANISASI, GAYA KEPEMIMPINAN, DAN KEPUASAN KERJA BERPENGARUH TERHADAP KOMITMEN ORGANISASI KARYAWAN - Yoga Pratama, Gst. Md. Ngr. Tyas Febri; Suwandana, I Gusti Made (E-Jurnal Manajemen; Vol 9 No 2 (2020)DO - 10.24843/EJMUNUD.2020.v09.i02.p09, 2020)
The research aims to obtain empirical evidence about the influence given by variables such as organizational culture, leadership style, and job satisfaction on the organizational commitment of employees who are members of a Balinese souvenir company, Cening Ayu in Batubulan, Gianyar. The study population was all company employees, amounting to 60 people. The sample is determined using the saturated sample method, so that the entire population is used as a research sample. Research data were analyzed using multiple linear regression techniques. The results showed that the three variables, organizational culture, leadership style, and job satisfaction had a positive and significant influence on the organizational commitment of a Balinese souvenir company, Cening Ayu in Batubulan, Gianyar. Keywords: organizational culture; leadership; job satisfication; commitment